The edge of law : legal geographies of a war crimes court / Alex Jeffrey, University of Cambridge. - Jeffrey, Alexander Sam (Cambridge studies in law and society., 2020)
The Edge of Law explores the spatial implications of establishing a new legal institution in the wake of violent conflict. Using the example of the establishment of the War Crimes Chamber of the Court of Bosnia and Herzegovina, Alex Jeffrey argues that legal processes constantly demarcate a line of inclusion and exclusion: materially, territorially and corporally. In contrast to accounts that have focused on the judicial outcomes of these transitional justice efforts, The Edge of Law draws on long-term fieldwork in Bosnia and Herzegovina to focus on the social and political consequences of the trials, tracing the fraught mechanisms that have been used by international and local political elites to convey their legitimacy. This book will be of interest to socio-legal and geographical scholars working in the fields of transitional justice, legal systems, critical geopolitics and criminology.